Does trajectory matter? A study looking into the relationship of trajectory with target engagement and error accommodation in subthalamic nucleus deep brain stimulation - Steel, David Anthony; Basu, Surajit (Springer, 2017)
Background: STN-DBS is now a key treatment choice for advanced Parkinson’s disease. The optimum target area within the STN is well established. However, no emphasis on the impact of trajectory exists. The ellipsoid shape of the STN and the off-centre traditional target point mean that variation in the electrode inclination should affect STN engagement. Understanding of this relationship could inform trajectory selection during planning by improving STN engagements and margins for error. Methods: We simulated electrode placement at the clinical target through a set of trial trajectories. Twelve 3D-reconstructed STNs were created from MRI data of 6 patients. An appropriate target within each STN was then chosen. Each STN was approached through 56 simulated trajectories arranged in a grid covering a quadrant of skull around and in front of the coronal suture. A subset of 20 viable trajectories was reassessed for depth of engagement in each STN whilst approaching the chosen target. Results: Group averages for each trajectory are presented as traffic light maps and as an overlaid skull mask illustrating recommended electrode entry sites. Trajectories under 30 degrees anterior to the bregma and between 10 to 30 degrees off the midline accommodated over 2.4 degrees of wobble. A mean engagement of 6 mm was possible in half of the subset. The longest engagements are on trajectories which saddle the coronal suture, extending to 40 degrees lateral. Microelectrode tracts of 14 additional STNs were collated using above protocol and engagement exceeded 5 mm in all central trajectories without capsular side effects, suggesting placement away from STN borders. Conclusions: Trajectory selection influences engagement and flexibility to accommodate electrode wobble or brain shift whilst approaching a chosen STN target. We recommend having the first trial trajectory 20 degrees anterior to the bregma, moving postero-laterally in successive trials to balance both error and engagement. When wider margins for error are beneficial (e.g. second side during bilateral procedures), trajectories nearer the coronal suture and around 25 degrees off the midline are advised.